Privatfinanzierung der Verkehrsinfrastruktur. Gutachten vom März 2005. - (:unkn) unknown (Deutscher Verkehrs-Verl., 2005)
The Scientific Advisory Council for Transport of the Federal Ministry of Transport, Construction Industry and Housing has presented its expert opinion about using private sector funds to pay for transport infrastructure projects. It considers it necessary and sensible to switch from tax revenues to users' funds. Any increase in the involvement of private management will lead to actual savings in the areas of design, planning and construction, thus creating a more solid base for the provision of finance for transport routes. Whereas overall planning of transport routes is the task of the state, any projects beyond this should - as far as feasible - be allotted to private sector companies. The DBFO (Design, Build, Finance, Operate) model can provide the necessary guidance. Measures are needed to safeguard common standards for those sections of the transport network for which private carriers are responsible, by taking into account the different cost and demand structures. The Council has recommended the involvement of all user groups in the final financing arrangements which, in the case of Germany, should also include smaller trucks, busses and private cars in addition to lorries. To preempt any potential moves by the transport sector to avoid paying toll charges, not only the use of federal motorways should be subject to a toll payment but also federal trunk roads of interregional importance. It is deemed indispensable to apply strict rules about the use of the revenue gained from road tolls in order to further private management initiatives and users' acceptance of such charges. Intermodal transfers should only be justified in exceptional cases. The Council has pointed out that any moves towards new approaches to transport project funding will make it necessary to create new institutions and enhance statutory laws. difu
Keywords: Verkehr; Verkehrsweg; Verkehrsplanung; Verkehrsinfrastruktur; Finanzierung; Straßenverkehr; Schienenverkehr; Luftverkehr; Öffentliche Aufgabe; Privatsektor; Privatfinanzierung; Nutzungsentgelt; Konzessionsmodell; Betreibermodell; Public-Private-Partnership; Erfahrung; International; Rahmenbedingung; Verkehrsträger